Combined optogenetic and electrical stimulation of the sciatic nerve for selective control of sensory fibers - Matarazzo, Jerico V.; Ajay, Elise A.; Payne, Sophie C.; Trang, Ella P.; Thompson, Alex C.; Marroquin, Jason B.; Wise, Andrew K.; Fallon, James B.; Richardson, Rachael T. (Frontiers in Neuroscience, 2023)
Introduction Electrical stimulation offers a drug-free alternative for the treatment of many neurological conditions, such as chronic pain. However, it is not easy to selectively activate afferent or efferent fibers of mixed nerves, nor their functional subtypes. Optogenetics overcomes these issues by controlling activity selectively in genetically modified fibers, however the reliability of responses to light are poor compared to electrical stimulation and the high intensities of light required present considerable translational challenges. In this study we employed a combined protocol of optical and electrical stimulation to the sciatic nerve in an optogenetic mouse model to allow for better selectivity, efficiency, and safety to overcome fundamental limitations of electrical-only and optical-only stimulation. Methods The sciatic nerve was surgically exposed in anesthetized mice (n = 12) expressing the ChR2-H134R opsin via the parvalbumin promoter. A custom-made peripheral nerve cuff electrode and a 452 nm laser-coupled optical fiber were used to elicit neural activity utilizing optical-only, electrical-only, or combined stimulation. Activation thresholds for the individual and combined responses were measured. Results Optically evoked responses had a conduction velocity of 34.3 m/s, consistent with ChR2-H134R expression in proprioceptive and low-threshold mechanoreceptor (Aα/Aβ) fibers which was also confirmed via immunohistochemical methods. Combined stimulation, utilizing a 1 ms near-threshold light pulse followed by an electrical pulse 0.5 ms later, approximately halved the electrical threshold for activation (p = 0.006, n = 5) and resulted in a 5.5 dB increase in the Aα/Aβ hybrid response amplitude compared to the electrical-only response at equivalent electrical levels (p = 0.003, n = 6). As a result, there was a 3.25 dB increase in the therapeutic stimulation window between the Aα/Aβ fiber and myogenic thresholds (p = 0.008, n = 4). Discussion The results demonstrate that light can be used to prime the optogenetically modified neural population to reside near threshold, thereby selectively reducing the electrical threshold for neural activation in these fibers. This reduces the amount of light needed for activation for increased safety and reduces potential off-target effects by only stimulating the fibers of interest. Since Aα/Aβ fibers are potential targets for neuromodulation in chronic pain conditions, these findings could be used to develop effective strategies to selectively manipulate pain transmission pathways in the periphery.